2013
DOI: 10.4314/ajtcam.v10i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial activity of some plants growing in Algeria: <i>Juglans Regia, Lawsonia inermis and Salvia officinalis.</i>

Abstract: The current study was undertaken to evaluate in vitro the antileishmanial activity of three plants growing wild in Algeria : Juglans regia, Lawsonia inermis and Salvia officinalis. The hydroalcoholic extracts of these plants were tested on the growth of the promastigotes of Leishmania major. The plant extract effects were compared with three controls : CRL1 composed of 1 ml RPMI inoculated with 10 6 of promastigotes, CRL2 composed of 1 ml RPMI inoculated with 10 6 of promastigotes and 100 μl of hydroalcoholic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
1
12
0
2
Order By: Relevance
“…A hydroalcoholic extract of a Nigerian S. officinalis showed total inhibition of the L. major growth with reducing the number of their promastigotes (Serakta et al 2013).…”
Section: Antileishmanial Activitymentioning
confidence: 99%
“…A hydroalcoholic extract of a Nigerian S. officinalis showed total inhibition of the L. major growth with reducing the number of their promastigotes (Serakta et al 2013).…”
Section: Antileishmanial Activitymentioning
confidence: 99%
“…The in vitro antileishmanial activity of the hydroalcoholic extract of Lawsonia inermis was tested on the growth of the promastigotes of Leishmania major. The results showed that Lawsonia inermis extracts reduced the promastigotes number significantly (p<0.01) [91]. The 90% ethanolic extract of Lawsonia inermis leaves was investigated for anticoccidial effects against caecal coccidiosis in broilers.…”
Section: Antiparasitic Effectsmentioning
confidence: 99%
“…The lymphocytes were isloated according to the method outlined by Bøyum [15,17]. Extracts were added at concentrations of 100, 50, 25 and 10 µg/mL in DMSO.…”
Section: Cytotoxicity Testmentioning
confidence: 99%